Health literacy and health outcomes among older patients suffering from chronic diseases: A moderated mediation model - Lu, Jinjin; Sun, Shuting; Gu, Yechun; Li, Huihui; Fang, Liangyu; Zhu, Xiaoling; Xu, Hongbo (Frontiers in Public Health, 2023)
This study aimed to determine whether self-efficacy for managing chronic disease mediates the relationship between health literacy and health outcomes among older patients with chronic diseases, and to explore whether disease duration moderates the relationship between health literacy, self-efficacy for managing chronic disease, and health outcomes. Participants were recruited from tertiary hospitals in Zhejiang Province, China from May 2019 to June 2020 using a convenience sampling method. A total of 471 older patients with chronic diseases completed questionnaires measuring demographics, disease-related information, health literacy, self-efficacy for managing chronic disease, and health outcomes. The mediation effect was examined using the structural equation model method, based on the bias-corrected bootstrapping method. The moderation effect was tested by the multiple group analysis. A good fit model suggested that self-efficacy for managing chronic disease partially mediated the relationships between health literacy and health outcomes. In addition, disease duration moderated the relationships between health literacy, self-efficacy for managing chronic disease, and health outcomes. Findings highlight that adequate health literacy improved health outcomes among older patients with chronic diseases, which was further promoted by self-efficacy for managing chronic disease. Moreover, a long disease duration could enhance the effect.